Acclimation of Arabidopsis thaliana to the light environment: the relationship between photosynthetic function and chloroplast composition. - Bailey, S; Horton, P; Walters, R (2004)
Plants respond to growth under different environmental conditions by adjusting the composition of the photosynthetic apparatus. To investigate the consequences of the acclimation strategies adopted by Arabidopsis thaliana, we have assessed the functioning of the photosynthetic apparatus in plants with very different chloroplast compositions. Using chlorophyll fluorescence analysis, we have determined the efficiency of, and capacity for, electron transport, assessed the ability to undergo state transitions, and measured non-photochemical quenching over a range of actinic irradiances followed by its resolution into fast- and slow-relaxing components; parallel measurements of leaf carotenoid composition were also carried out. The data clearly show that acclimation serves to maintain the electron transport chain in an oxidised state, ensuring efficient photochemistry. Furthermore, plants grown in high light have a greater capacity for energy-dependent feedback de-excitation, but this is not correlated with xanthophyll cycle pigment levels or de-epoxidation state. Surprisingly, even plants with very low levels of light-harvesting complexes were able to undergo state transitions. We also show that apparent discrepancies between chloroplast composition and photosynthetic function can be attributed to varying degrees of light penetration through the leaf. Thus, leaf chlorophyll content is an important factor influencing acclimation within the leaf.